1101 words Picture Dictionary - Dhingra's (Uttar Pradesh Dhingra's, 2002)
1101 WORDS Picture Dictionary || This book is very good || During children's formative years, they want more and more information about the things see around them, and the people they come across. For this they need the knowledge of correct words. A good vocabulary can be built during these formative years. It will build the confidence in both spellings and grammar. Clear definitions and sentences are provided to the children.suitable Pictures are given to make the meanings clear to the children.words are grouped alphabetically.